A paradox of knowledge management in the case of a Japanese retail company. (19th April 2004) - Shinozaki, Kaori; Nagata, Akiya
This paper attempts to show a paradox relating to the introduction of knowledge management, by the case study of Japan's retail company. When companies introduce knowledge management, if the reasons for establishing knowledge databases are seen only in terms of improving the efficiency of knowledge utilisation, there is a risk that competitiveness will be reduced due to the resulting loss of resources of experience-based knowledge.